From Support to Success: How Perceived Organizational Support Drives Change Readiness and Performance in Public Universities (International Journal of Latest Technology in Engineering Management & Applied Science, 2025)
This study investigates how perceived organizational support (POS) influences job performance (JP) directly and indirectly through readiness to change (RTC) among nonacademic civil servants in Indonesian public universities. Drawing upon the Organizational Support Theory and the Change Readiness framework, this research analyzes responses from 180 administrative employees at Universitas Mulawarman undergoing institutional transformation. Using Partial Least Squares Structural Equation Modeling (PLS-SEM), this study found that POS significantly enhanced both RTC and JP. Moreover, RTC positively influenced JP and mediated the relationship between POS and JP. These findings confirm that organizational support is a vital antecedent to fostering individual psychological readiness, which in turn promotes adaptive and productive behaviors during periods of change. The study contributes to the literature by integrating POS and RTC into a cohesive explanatory model of employee performance within public higher education institutions. The results highlight the need for policy strategies that emphasize inclusive change communication, supportive leadership, and long-term investment in human capital to improve organizational readiness and performance. The limitations of this study include the single-institution sample and cross-sectional design. Future research may explore comparative analyses across multiple institutions and adopt a longitudinal or mixed-method approach to capture the dynamic processes of organizational transformation.